High number harmonic exitation by oscillators in periodic media and in periodic potential - Buts, V.A.; Kornilov, E.A. (Вопросы атомной науки и техники, 2003)
The some results of theoretic and experimental investigations about excitation high number harmonics by non-relativistic oscillators are represented in this report. Were shown that in media, which has even small periodic heterogeneity of dielectric permeability or potential, non-relativistic oscillators can radiate as relativistic particles. They can efficiency radiate high number harmonics. The theory as one particle radiation as selfconsistent nonlinear theory radiation of oscillator ensemble was created. The experimental results confirm the main results of theory. In particularly, there was exited ultraviolet radiation in experiment, when on a crystal intense ten-centimetric radiation was acting.